2020
DOI: 10.1088/1757-899x/821/1/012032
|View full text |Cite
|
Sign up to set email alerts
|

Computational thinking digital media to improve digital literacy

Abstract: Computational Thinking (CT) has been defined as an important skill that supports digital literacy in the industrial revolution 4.0. Computatiomal Thinking contained in the informatics curriculum is classified as local content for several formal schools. Four key techniques (cornerstones) to Computational Thinking consist of abstraction, algorithm, decomposition and pattern recognition, are very important in the processes involved in formulating problems and the solutions so that the solutions are represented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The target population for this particular study was SMA 3 Palangka Raya students. Several instruments were used to obtain data (Novitasari et al, 2023); (Yuliana et al, 2020). The results of this study SMA 3 Palangka raya show that the overall activity, content, and characteristics of the science and mathematics story based on digital learning directly lead to the improvement of the problem-solving phase, namely 1) formulation of the problem, 2) identification of problem-solving strategies, 3) exploration of possible strategies, 4) evaluation of the effectiveness and impact of problem solving It was shown that story development and examples of how the characters solve the problems encountered in the story are the main factors that cause the improvement of problemsolving skills (Munte & Korsina, 2022;Siburian et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The target population for this particular study was SMA 3 Palangka Raya students. Several instruments were used to obtain data (Novitasari et al, 2023); (Yuliana et al, 2020). The results of this study SMA 3 Palangka raya show that the overall activity, content, and characteristics of the science and mathematics story based on digital learning directly lead to the improvement of the problem-solving phase, namely 1) formulation of the problem, 2) identification of problem-solving strategies, 3) exploration of possible strategies, 4) evaluation of the effectiveness and impact of problem solving It was shown that story development and examples of how the characters solve the problems encountered in the story are the main factors that cause the improvement of problemsolving skills (Munte & Korsina, 2022;Siburian et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The results of other studies also provide information to us, relating to digital literacy capabilities that significantly differences learning achievement in high school students [30]. Then research conducted at the elementary school level provides information, that each respondent interviewed, that they realize with digital literacy skills will make it easier for them to learn online [31]. The results of studies from various levels of education strengthen that when the learning process is carried out online, the role of digital literacy skills is very important for students' success in achieving learning goals.…”
Section: IIImentioning
confidence: 94%
“…Network media complex is often manifested as an intricate psychological state [7]. Along with the demand and use of the network, as well as the network emotion continuously strengthened in this process [8][9][10]. Based on their dependence and persistence on the Internet, teenagers form a collection of network needs, network emotions and network consciousness in their subconsciousness, which has an influence and control effect on their thoughts, wills and behaviors [11].…”
Section: Introductionmentioning
confidence: 99%